Bear likes to share - Shea, Therese (New York : Rosen, 2006)
Illustrations and simple text introduce new vocabulary words and tells a story about Bear, who shares his baskets of berries with others.
"Fantasy/Fairy tale"--Cover p. [4].
1.2
K-3
K-3
BR80L
Keywords: Bears -- Juvenile fiction; Sharing -- Juvenile fiction; Bears -- Fiction; Sharing -- Fiction; Bears -- Fiction; Sharing -- Fiction